Pengembangan Tes Diagnostik Berbentuk Uraian Berdasarkan Ranah Kognitif untuk Mengetahui Letak Kesulitan Belajar Siswa SMP pada Materi Bangun Ruang - Anggita Oktaviana Putri (LP3M IAI Al-Qolam Malang, 2021)
Often students have difficulty learning mathematics from elementary to college level. Student’s Learning difficulties in mathematics must be addressed soon because it will affect the students' mathematical thinking ability. This study aims to develop the tests that can diagnose which part of student’s learning difficulties, especially on the building curved side space. The development of tests is based on revived Bloom's cognitive rate of taxonomy that is remembering, understanding, applying, analyzing, evaluating and creating. This study development uses the Plomp development model through three stages: 1) preliminary research, 2) prototyping phase, and 3) assessment phase. Results from the development of diagnostic test instruments meet valid, reliable, and practical. Thus a diagnostic test developed could be used as an alternative in knowing the part of student difficulties.